2016
DOI: 10.1111/cch.12360
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of the German version of the Children's Assessment of Participation and Enjoyment (CAPE) and Preferences for Activities of Children (PAC)

Abstract: The German version of the PAC showed satisfactory reliability; however, reliability was not satisfactory for all scores of the CAPE, but comparable with versions in other languages. The need for newly developed participation measurements requires further discussion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(33 citation statements)
references
References 28 publications
1
32
0
Order By: Relevance
“…The CAPE [ 41 ] was developed and has been shown to have adequate validity and reliability in English [ 42 , 43 , 44 ]. Internal consistency and test-retest reliability have been confirmed in Dutch [ 45 ], Greek [ 46 ], Spanish [ 47 , 48 ], Swedish [ 49 ], Chinese [ 50 ] and Norwegian [ 51 ]. However, the need for cultural validation (in addition to translation) has been highlighted by various authors [ 48 , 49 , 50 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…The CAPE [ 41 ] was developed and has been shown to have adequate validity and reliability in English [ 42 , 43 , 44 ]. Internal consistency and test-retest reliability have been confirmed in Dutch [ 45 ], Greek [ 46 ], Spanish [ 47 , 48 ], Swedish [ 49 ], Chinese [ 50 ] and Norwegian [ 51 ]. However, the need for cultural validation (in addition to translation) has been highlighted by various authors [ 48 , 49 , 50 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Supportive evidence for the construct validity was obtained from prediction correlation with child and family variables (27, 30), and quality of life domains (31). Test-retest reliability was satisfactory (3032). A systematic review showed that the CAPE is a valid participation measure for CP children (33).…”
Section: Introductionmentioning
confidence: 92%
“…A systematic review showed that the CAPE is a valid participation measure for CP children (33). Translated and adapted versions have been validated (3032, 34, 35), thereby allowing comparisons between countries (22, 36).…”
Section: Introductionmentioning
confidence: 99%
“…Answers are (1) I would not like to do it at all, (2) I would sort of like to do it, and (3) I would really like to do it [29]. The outcome of the CAPE/PAC has demonstrated evidence for reliability and validity in several countries, including Sweden [36][37][38][39].…”
Section: Assessment Instruments and Outcome Measures Thementioning
confidence: 99%